STATUS HUKUM ISTERI DARI PERKAWINAN SIRI YANG DICERAIKAN MELALUI SHORT MESSAGE SERVICE (SMS) DITINJAU DARI HUKUM ACARA PERADILAN AGAMA - Ezra Efendi Walenta, Ade; R., Ibrahim (Kertha Wicara : Journal Ilmu Hukum, 2013)
The legal status of marriage siri wife divorced via short message service (SMS) in terms of religious law court proceedings, written with the aim of understanding the legal status of marriage siri wives who divorced through SMS. In writing this paper using normative research methods. Conclusion of the writing of this manuscript is the legal status of the wife of a divorced marriage is the single via SMS.
Keywords: siri marriage, legal status of wife, divorced